Evaluation as Econometrics of the Relationship between Unemployment and Economics Growth in Turkey (Okun's Law Case) - Gülistan Erdal; Gungor Karakas; Hasan Gökhan Doğan (Journal of New Results in Science)
– In this study, relationship between unemployment and economic growth in Turkey was investigated. The study, which was carried out in the period 1988-2012, was evaluated. In order to explain relationship between unemployment and economic growth, Vector Autoregressive Model, Jhonsen Cointegration Analysis and Granger Causality/Block Exogeneity Test were used. As a result, a relationship between unemployment and GDP in Turkey was determined as foresee of Okun’s Law and direction of relationship can periodically vary. Affected employment of economic growth is known to be linked to certain conditions. According to this situation economic growth must be explained and unemployment cannot be prevented with a high growth rate which case should be considered. That balanced of nature unemployment rate with optimal growth rate can be evaluated as rational foresight